Operation of police equipment on duty under martial law - T. V. Shevchenko; F. F. Zurov; P. M. Frolenkova (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The article examines the problematic issues of operation of police equipment during the service of ensuring public security and order under the legal regime of martial law, shows the current state of modern research on the topic, and outlines the main problems faced by police officers when operating equipment. The publications on this topic are reviewed, and the regulatory framework of the MIA of Ukraine on the analysed issue is also studied.Based on the analysis of police uniforms and a survey of police practitioners, a list of equipment most often used by police officers during service has been compiled, taking into account the peculiarities of service under martial law and the experience gained in 2022–2023. Additionally, the weight characteristics of the specified sets of equipment for police officers was developed and presented regarding their equipment before and after the introduction of martial law.The research has concluded that the lack of regulations and standards for equipment complicates the work of police officers, who have to use it without specific instructions. Police officers are forced to use their own experience and information available on the Internet, which can have a negative impact on their safety. Improper placement or incorrect use of equipment can endanger the life and health of police officers. Wearing the equipment incorrectly can lead to physical problems such as discomfort, restricted movement, overheating and poor ventilation, which can increase the risk of injury and strain. This can have a negative impact on the physical and psychological health of police officers and their work performance.